Mixed method research on football coaches` competitive behavior - Rodrigues, J.; Rodrigues, F.; Resende, R.; Espada, M.; Santos, F. (Frontiers in Psychology, 2021)
Objective: The purpose of this study was to present the reliability of three validated measures, namely the System of Analysis of Instruction in Competition, the Questionnaire on Coach Instructional Behavior Expectations, and the Questionnaire on Coach Instructional Behavior Perception that could be used in a mix-method approach.